2004
DOI: 10.1104/pp.104.040477
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects of Plant Adaptation to Life in the Chernobyl Zone

Abstract: With each passing year since the Chernobyl accident of 1986, more questions arise about the potential for organisms to adapt to radiation exposure. Often this is thought to be attributed to somatic and germline mutation rates in various organisms. We analyzed the adaptability of native Arabidopsis plants collected from areas with different levels of contamination around the Chernobyl nuclear power plant from 1986 to 1992. Notably, progeny of Chernobyl plants resisted higher concentrations of the mutagens Rose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(108 citation statements)
references
References 27 publications
4
99
1
3
Order By: Relevance
“…A lack of change in expression of Brca1 in bank voles from the CEZ indicates that the homologous recombination repair pathway is not a key component of the response to environmental radionuclides, consistent with a recent study of expression of DBS repair pathways during exposure to IR (Liu et al, 2016). Arabidopsis from the CEZ show reduced recombination, which might prevent gross chromosomal rearrangements (Kovalchuk et al, 2014).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…A lack of change in expression of Brca1 in bank voles from the CEZ indicates that the homologous recombination repair pathway is not a key component of the response to environmental radionuclides, consistent with a recent study of expression of DBS repair pathways during exposure to IR (Liu et al, 2016). Arabidopsis from the CEZ show reduced recombination, which might prevent gross chromosomal rearrangements (Kovalchuk et al, 2014).…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, a change in fur color of bank voles within the CEZ was attributed to downregulation of pheomelanin to reallocate antioxidants to ROS defense (Boratynski et al, 2014). Indeed, upregulation of oxidative stress response genes Cat and Fsd3 in Arabidopsis (Kovalchuk et al, 2014) indicate that increased ROS defense could be a key coping strategy against exposure to environmental radionuclides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies of repair inhibitions, dose-effect relationships for low-and high-LET radiations, measurements of unscheduled DNA synthesis and an efficacy of the single strand breaks recovery [15] suggest that the divergence of populations in terms of resistance is connected with a selection for changes in the effectiveness of repair systems. Another study on the possible mechanisms of adaptations to radioactive contamination [16] showed extremely low (more than 10-fold) recombination levels, and a higher level of global genome methylation in chronically irradiated plants that may have prevented extensive genome rearrangements. Although our understanding of mechanisms of adaptation is far from complete, these studies give good evidence that the response of biological systems to stress have been produced by normal evolutionary processes in relation to the environments in which the populations occur.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the hierarchy of different biological processes operative from molecules to biomes, the rate of biological adaptation is difficult to predict. While molecular and physiological processes can occur within minutes to days and months, biome-level processes typically take tens of years to even millions of years (Kowalchuk et al 2004;Gienapp et al 2008;Carroll et al 2016). The crucial question is whether biological adaptation is fast enough to cope with global climate change (Stocker et al 2013).…”
Section: Introductionmentioning
confidence: 99%